Twilight for the gods - Gann, Ernest Kellogg, 1910-1991 (W. Sloane Associates, 1956)
Ship sailing for Mexico with cargo of copra carries a few passengers - a missionary, a Russian-Jewish couple, and a planter's widow. All of whom derive moral courage from an ordeal.